Duration of exclusive breastfeeding and subsequent child feeding adequacy. - Aryeetey, R.N.; Goh, Y.E. (Ghana medical journal, 2013)
Mothers of young children in Ghana believe that breastfeeding exclusively for six months impairs subsequent introduction of other foods. The current study was designed to determine whether feeding adequacy among 9-23 months old children is influenced by duration of exclusive breastfeeding. We surveyed 300 mother-infant pairs attending child-welfare-clinic at the University of Ghana Hospital, Accra. Data collected included sociodemographic characteristics, morbidity, breastfeeding history, and maternal practices and perception on child feeding and temperament. Current child feeding was assessed using 24-hour dietary recall. Adequately fed children were defined as 9-23 month old children meeting three basic feeding adequacy thresholds: 1) was fed complementary foods, at least three times in the last 24 hours, 2) was fed from at least three food groups, and 3) received breast milk in the last 24 hours. Multiple logistic regressions were used to identify independent predictors of child feeding adequacy. About 66% of children were exclusively breastfed for six months and only 56% were adequately fed in the in the 24 hours preceding the survey. Child feeding adequacy was unrelated to duration of exclusive breastfeeding (OR=0.73; p=0.30). After controlling for child sex, age, and maternal education, the independent determinants of feeding adequacy included recent child morbidity (OR=0.41; p=0.03), number of caregivers who feed child (OR=1.33; p=0.03), and maternal perception that child does not like food (OR=0.25; p<0.01). Child temperament was unrelated to feeding adequacy. Child feeding adequacy is not affected by duration of exclusive breastfeeding. The study provides evidence to address misperceptions about exclusively breastfeeding for six months.
Keywords: child; dietary diversity; Exclusive breastfeeding; feeding adequacy; duration